A comparative study of three palatoplasty techniques in wide cleft palates. Issue 2 (February 2021) - Sakran, K.A.; Liu, R.; Yu, T.; Al-Rokhami, R.K.; He, D.
Abstract: The aim of this study was to clinically evaluate the effectiveness of various palatoplasty techniques for the repair of cleft palates greater than 8 mm in width. This prospective cohort study included 142 patients with complete cleft palate between September 2017 and January 2019. Among the patients, 60 underwent a modified palatoplasty with Furlow Z-plasty (MPFZP), 51 underwent a von Langenbeck (VL) repair, and 31 underwent a two-flap palatoplasty (2FP). The MPFZP technique was modified with bilateral relaxing incisions and a radical intravelar veloplasty. Descriptive statistics and the χ 2 test were used to explore and compare the rates of complications among the three surgical techniques. No statistically significant difference in sex, age at repair, cleft width, or cleft Veau type was found among the three groups. Rates of wound dehiscence at 1 week and fistula formation at 3 months after the surgery also did not differ significantly among the three techniques. However, velopharyngeal function for speech was better in patients who underwent MPFZP compared to the other two techniques ( P  < 0.05). The repair of a wide cleft palate can be difficult due to the tension at closure. Although the study findings did not demonstrate a difference in complication rates among the three techniques, MPFZP appears to have the best functional outcomes in patients with a cleft palate wider than 8 mm.